HUBUNGAN PERSONAL HIGIENE DENGAN PENCEGAHAN SCABIES PADA MASYARAKAT YANG BEROBAT DI PUSKESMAS TATELU KECAMATAN DIMEMBE KABUPATEN MINAHASA UTARA - Sankup, Christin (Journal Of Community & Emergency, 2024)
Scabies (scabies) is a contagious skin disease caused by Sarcoptes scabiei hominis variant (a type of tick, mite), characterized by complaints of itching, especially at night and transmitted through direct or indirect contact through used bedding or clothing. Scabies is an infestation of human skin caused by the penetration of the obligate parasite, S. scabiei var hominis into the epidermis (Stone et al., 2018). Scabies is caused by S. scabiei, transmitted by fertilized female lice. Fleas can live outside the skin for only 2-3 days at room temperature 210 C with a relative humidity of 40-80%. Female lice measure 0.3-0.4 microns, male lice fertilize female lice and then die, then these female lice will dig a hole into the epidermis and then make a tunnel in the stratum corneum, and lay their eggs in the tunnel. The purpose of the study was to determine the relationship between personal hygiene and prevention of scabies in the community seeking treatment at the Tateli Public Health Center, Minahasa Regency. This research is a quantitative type of research using a cross sectional study approach that is descriptive analytic in January 2022 and the place of research is in the Manado Class II Detention Center. The statistical test used is the "Chi-square" statistical test with a 95% confidence degree if . The results obtained that the P value = 0.009 while the value of = 0.05 so that the value of the Chi¬ Square statistical test results obtained p value = 0.007 < = 0.005 which indicates that Ha is accepted which means, there is a relationship between personal hygiene and the incidence of scabies. People who seek treatment at the Tatelu Health Center, Minahasa Regency. Conclusion From the results of the study, it can be seen that the results of personal hygiene research in people who seek treatment at the Tatelu Health Center have more personal hygiene that is not good. The incidence of scabies in the community who seek treatment at the Tatelu Health Center is more than not suffering from scabies. Suggestions in this study are that this research is expected to ensure that the warden on duty at the prison always maintains the cleanliness of the prison to keep the incidence of scabies from increasing.